2000
DOI: 10.1128/jcm.38.4.1592-1598.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polyvinyl Alcohol Fixative with Three Less Hazardous Fixatives for Detection and Identification of Intestinal Parasites

Abstract: Polyvinyl alcohol (PVA) containing the fixative mercuric chloride is considered the “gold standard” for the fixation of ova and parasites in the preparation of permanently stained smears of stool specimens. However, mercuric chloride is potentially hazardous to laboratory personnel and presents disposal problems. We compared three new alternative, nontoxic fixatives with PVA, analyzing ease of sample preparation and quality of smears. Sixty-eight fresh stool specimens were divided into aliquots and placed in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 3 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…Only fresh samples were collected (from their inner part to avoid soil contamination), any potentially rain‐ “washed” or old (>12 hr) samples were discarded. Approximately 5 g of each sample was immediately fixed in a 13 ml single vial tube of PROTOfix™ CLR (Alpha‐tech‐Systems, Inc., Vancouver, WA) according with the manufacturer's instructions [Jensen et al, ] and stored at room temperature until they were shipped under international permits to the Department of Pathology and Parasitology of the Veterinary and Pharmaceutical University, Brno, Czech Republic.…”
Section: Methodsmentioning
confidence: 99%
“…Only fresh samples were collected (from their inner part to avoid soil contamination), any potentially rain‐ “washed” or old (>12 hr) samples were discarded. Approximately 5 g of each sample was immediately fixed in a 13 ml single vial tube of PROTOfix™ CLR (Alpha‐tech‐Systems, Inc., Vancouver, WA) according with the manufacturer's instructions [Jensen et al, ] and stored at room temperature until they were shipped under international permits to the Department of Pathology and Parasitology of the Veterinary and Pharmaceutical University, Brno, Czech Republic.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have indicated that some less hazardous mercury-free fixatives might be substitutions for traditional fixing agents. [16][17][18][19] The objective of the present study was to determine whether in vitro culture could be another totally environmentally safe method of choice for diagnosing B. hominis infection for clinical and epidemiological purposes. Growth characteristics of B. hominis in vitro in three commercially available monophase liquid media, Roswell Park Memorial Institute (RPMI) 1640 medium (10.4 g, Gibco BRL), 199 Medium (9.5 g, Gibco BRL), and Dulbecco's modified Eagle's medium (DMEM; 13.4 g, Gibco BRL), were observed and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Then, all stool samples kept in dry universal bottles were sent immediately to the Delomena Hospital Laboratory, Mena town, Ethiopia, for further studies. Ritchie's fecal concentration technique (Ritchie, 1948) and polyvinyl alcohol fixation of stools were carried out to obtain maximum sensitivity (Jensen et al, 2000). The fresh stool specimen was preserved with polyvinyl alcohol, and kept cool (4°C).…”
Section: Data Collection and Analysismentioning
confidence: 99%